Pengaruh Skeptisme Profesional dan Independensi terhadap Kinerja Auditor pada Masa Pandemi COVID-19 - Cikita Dasty Sirait, Grace Priskila; Maria, Evi (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to find empirical evidence of the influence of professional skepticism and independence on the performance of auditors carrying out assignments during the COVID-19 pandemic. The primary data was obtained by distributing questionnaires to auditors working at Public Accounting Firms in Semarang City who received audit assignments from 2020 to 2022. The total research sample was 88 respondents. Data analysis in this study used multiple regression analysis, and the data was processed using SPSS version 25. The study found that professional skepticism and independence positively affected auditors' performance in Semarang City during the pandemic. Professional skepticism and independence influenced auditor performance during the COVID-19 pandemic by 31.8 percent. Additional test results by adding gender and work experience as control variables found consistent results that there was a positive influence between professional skepticism and independence on auditor performance during the pandemic. In contrast, gender and work experience did not affect auditor performance in Semarang City during the pandemic. These findings confirm the attribution theory that the performance of auditors in Semarang City is influenced by inherent factors, namely professional skepticism and independence, even though audit assignments during the pandemic were carried out by auditors remotely.